The impact of Methicillin-Resistant Staphylococcus aureus (MRSA) evolution on clinical, phenotypic and genotypic characteristics of MRSA strains isolated in a tertiary teaching hospital / Sit Pik San - Sit, Pik San (2018)
Methicillin-resistant Staphylococcus aureus (MRSA) is a notorious bacterial pathogen causing well-publicized healthcare-associated (HA) and community-associated (CA) infections. Vancomycin has been used as the primary treatment for MRSA infections. However, reduced vancomycin susceptibility and vancomycin MIC creep have been described in many studies. Furthermore, the emergence of CA-MRSA isolates which cause nosocomial infections and HA-MRSA isolates circulating in the community has also been reported. In spite of that, only limited studies were done in monitoring the trends in MRSA infections in Malaysian hospitals. Therefore, this study attempted to characterized HA– and CA-MRSA infections using phenotypic and genotypic approaches. In addition, the changing epidemiology and the evolution of HA- and CAMRSA strains isolated from 2011 to 2013 were also assessed and correlated with patient’s clinical data. A total of 278 MRSA strains from year 2011 to 2013 collected from a tertiary teaching hospital in Malaysia were studied. Overall, MRSA acquisitions were significantly high in patients more than 50 years of age and male gender. Sixty-five percent of HA-MRSA were found carrying SCCmec types I to V while 26.9% were CAMRSA strains that harboured SCCmec types III, IV and V. The presence of SCCmec types IV and V strains that caused nosocomial infections and SCCmec type III strains that associated with CA-infections were also observed. Majority of the strains were HAMRSA and belonged to SCCmec type III which were found to be persistent and remained as endemic strains in this hospital. The overall PVL-positive rate among the MRSA strains in this hospital was 1.8%. All 2013 MRSA strains were multidrug-resistant which showed high resistance towards erythromycin, gentamicin, ciprofloxacin and clindamycin. During the study period, no vancomycin MIC creep was detected based on iv the significant fluctuation in the rate of MRSA strains with vancomycin MIC ≥ 1.5 µg/mL (38.9% in 2011, 57.9% in 2012 and 56.5% in 2013). High vancomycin MIC was observed to be significantly associated with SCCmec type III. There was no significant association between the mortality rate and high vancomycin MIC. Age, gender, diagnosis, comorbidities and the infection severity scores were the independent factors associated with patient’s mortality. Among 158 MRSA bacteraemia episodes, 80.4% occurred in patients more than 50 years old, male gender and were caused by the HA-MRSA strains. The incidence of bacteraemia appeared to be mostly primary bacteraemia. In addition, diabetes mellitus, chronic kidney disease and hypertension were major comorbidities associated with bacteraemia. MRSA bacteraemia patients with SCCmec type IV strains were significantly associated with cardiovascular disease. Compared with other SCCmec types, MRSA bacteraemia with SCCmec type V strains were implant-related. These strains associated with bacteraemia were further subtyped by MLST which grouped strains into 13 sequence types and were assigned into 12 pulsotypes by PFGE. The most common pulsotype was pulsotype E which was exhibited by SCCmec type III-ST239 strains. The presence of MRSA clones such as ST152-I, untypeable- ST508, ST1-IV, ST1137-IV, ST5-V, ST45-V and ST951-V in this study were the first reported in Malaysia.